Peningkatan Literasi Ketenagakerjaan dan Kesiapan Memasuki Dunia Kerja bagi Masyarakat di Kelurahan Krobokan - Imanuel Kurniawan Arif Soetedjo; Zaenal Arifin; Wijayono Hadi Sukrisno (Fakultas Hukum Universitas Semarang, 2024)
This community service program aims to improve labor literacy and work readiness among the productive-age community in Krobokan Village, Semarang City. The urgency of this activity arises from the community’s limited understanding of workers’ rights and obligations, labor social security, as well as the practical skills needed to face job selection processes. The program was carried out through a socialization approach involving speakers from the Master of Law Program at Universitas Semarang (USM) and was complemented with pre-test and post-test instruments to measure its effectiveness. The results show a significant improvement, with participants’ average understanding increasing from 21% in the pre-test to 81.25% in the post-test, indicating a 60.25% increase. These findings highlight that structured, applicative, and locally oriented socialization activities can strengthen labor literacy while also enhancing community work readiness. Therefore, this program can serve as a relevant empowerment model to support the improvement of human resource quality at the local level. Keywords: Community service; Labor; Literacy; Socialization; Work readiness